Crime and Satanism – Mutual Relationship and Characteristics of Criminal Acts - Matković, Aleksandar B (Pravni zapisi, 2018)
This paper explores the relationship between Satanism and criminal acts related to that sphere which are frequent in criminal and judicial practice. Author proposes two definitions of a criminal act connected with the contemporary occultism, as well as definition of occult-related crime. He offers a review of the already existing classifications of the Satanism-related crime, after which he presents additional, legal-oriented typology. It is concluded that the crime associated with Satanism is extremely heterogenous and comprehensive category which includes many criminal acts whose presence in practice varies a lot. Those criminal acts could be directly and primarily motivated by some kind of Satanic doctrine; however, in most cases, real motivation for a crime lies outside of that matter. Author divides most common crimes into four wider categories, analyzing particular crime motives, modus operandi and other elements relevant from legal, criminalistic and criminological perspective. He points out that the most frequent criminal acts associated with the domain of Satanism/pseudosatanism are various types of vandalism (for example: graffiti containing Satanic and anti-christian messages, grave desecration, church vandalism, as well as damaging or destruction of varios religious monuments, sacred items and sacred places connected with Christian religion), whose usual perpetrators are adolescents. Regarding ritual sacrifices, in vast majority of cases, object of criminal act is some sort of animal. Unlike popular speculations, human sacrifices connected with Satanic ceremonies are extremely rare in practice. Absolute majority of registered murder cases (and other crimes against life, physical and sexual integrity, rights and freedoms of man and citizen) which were inicially (in the early stages of investigation, or simply by sensacionalistic media informing) pointed out as a possible examples of “ritualistic satanic crimes”, proved not to be primarily related with real or presumed Satanic interests of the perpetrator. Even in those cases which were indirectly connected with some elements of Satanism, personal characteristics and general life perspective of the perpetrator proved to play crucial role in the domain of motivation for a crime and its realization (f.e. existence of some of the common pragmatic crime motive, presence of various personality disorders, presence of psychosis etc). Author presents and analyses satanic-related clues typical for all sorts of crime, as well as clues which are significant for particular criminal acts. He underlines the existence of wide varietry of occult/satanic indicators, which could vary from the satanic and anti-christian symbols, textual messages, illustrations, numerological aspects etc, to the lesser visible indicators concerning time, place, method, means, purpose of particular criminal act and the like. Among other things, author concludes that proper recognition of those clues and indicators could be an important step towards understanding and successfully solving individual criminal case.